Comparison of subclinical neuronal injury by measuring neuron-specific enolase in patients with severe aortic stenosis treated with transcatheter aortic valve replacement or sutureless aortic valve replacement - Seyda Yilmaz, Ahmet; Kahraman, Fatih; Erkan, Hakan; Korkmaz, Levent; Riza Akyuz, Ali (Annals of Medical Research, 2021)
Aim: Severe aortic valve stenosis (SAVS) which causes angina pectoris, syncope, arrhythmias, and sudden cardiac death, may be treated with transcatheter aortic valve replacement (TAVR) or sutureless aortic valve replacement (SU-AVR). We aimed to predict subclinical neuronal injury (SNI) by measuring neuron-specific enolase (NSE) in patients who underwent the TAVR and the SU-AVR.Materials and Methods: This clinical trial was carried out between January 2015 and January 2017. A total of 53 patients who had severe aortic valve stenosis (SAVS) and underwent TAVR and SU-AVR were included. The Serum NSE level was measured just before and 24 hours after the procedure. Demographic variables, neurologic assessment findings, clinical and echocardiographic data, carotid ultrasounds reports, and laboratory findings were recorded.Results: A total of 53 patients were included the study. The mean age was 78.4±8.6 and 20 were man (37.7%). The mean age of the TAVR group was significantly higher than the SU-AVR group (82.9±4.7 vs 71.5±8.7, p0.001). The NSE level was significantly higher in the SUAVR group compared to the TAVR group after the procedure (21.15±10.25 vs 35.32±12.64, p0.001). Differences between before and after the procedure the National Institutes of Health Stroke Scale (NIHSS), demographic and echocardiographic variables were similar between the two groups.Conclusion: Serum NSE level was significantly higher in the SU-AVR group than the TAVR group Therefore, we may consider the SNI rate is higher as well. In patients who are at higher risk for neurological damage or have neurologic disease, TAVR may be a better treatment option instead of SUAVR.
Keywords: Neuron specific enolase (NSE); sutureless aortic valve replacement (SU-AVR); transcatheter aortic valve replacement (TAVR)